A pumpless liver-adipose model for studying metabolic dysfunction and drug responses - Zeinab Ebrahimian; Fatemeh Kalalinia; Amir Reza Ameri; Hossein Hosseinzadeh; Bibi Marjan Razavi; Seyed Ali Mousavi Shaegh (PLoS ONE, 2026)
Metabolic dysfunction is a primary driver of chronic diseases, such as obesity and type 2 diabetes. Developing in vitro models allows to understand metabolic mechanisms and develop effective treatments. To this end, a pumpless open-top co-culture (POCC) device to simulate liver–adipose tissue interactions was developed. The POCC comprises a four-chamber bioreactor with an open-top configuration and an easy-to-assemble cover cap. Rotational motion enabled perfusion of culture media among the interconnected chambers. HepG2 and 3T3-L1 cells were co-cultured and exposed to olanzapine (Olz), chlorogenic acid (CGA), and metformin (Met) for four days. Drug responses in the POCC were compared with those in 96-well monocultures. Assessments were conducted for glucose/triglyceride (TG) levels, lipid accumulation, and cell viability. While viability remained unchanged, Olz increased lipid content, extracellular glucose and TG levels in the POCC model, effects that CGA and Met mitigated. This practical and physiologically relevant platform offers a promising alternative for preclinical screenings that could be employed to study other multi-tissue interactions in various disease models.